Effects of Deep Brain Stimulation in the Subthalamic Nucleus on Neurocognitive Function in Patients With Parkinson's Disease Compared With Medical Therapy: A Meta-Analysis - Wang, Jiazhen; Pan, Ru; Cui, Ying; Wang, Zhigang; Li, Qinghua (Frontiers in Neurology, 2021)
Background: DBS has been shown to significantly effect motor symptoms in Parkinson's disease (PD). However, some studies have suggested that it may have adverse effects on patients' neurocognitive function. To clarify this operation’s effect on neurocognitive function, we collected studies containing neurocognitive function evaluation for qualitative and quantitative analysis. Methods: We searched relevant clinical studies through Pubmed and Embase databases and extracted and sorted out information such as sample size, postoperative scores, preoperative and postoperative evaluation interval, PD course, exclusion criteria, etc., from articles meeting the standards. The magnitude and variance of the DBS group’s combined effects and the drug therapy group in each neurocognitive domain were calculated and analyzed by the random-effects model. Results: Compared with the drug treatment group, the verbal fluency of patients in the experimental group was significantly decreased at least moderately (ES=-0.553), in which the phonemic fluency declines greatly (ES=-0.842), learning and memory ability was slightly decreased (ES=-0.305), and other neurocognitive functions were not significantly decreased. Conclusion: STN-DBS can affect the fluency of speech and damage learning and memory. Besides, there was no significant correlation between the above effects and disease progression itself, and it was more likely to be associated with STN-DBS. It is suggested that postoperative patients should be trained and evaluated regularly for their verbal fluency and learning and memory ability. The safety of STN-DBS is acceptable for the majority of patients with motor symptoms.